THE INFLUENCE OF EMOTIONAL BURNOUT ON CONFLICT BEHAVIOR STRATEGY SELECTION - Литвинчук, Наталя; Баша, Ольга (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2025)
The article presents the results of an empirical study on emotional burnout as a factor influencing the choice of conflict behavior strategies in adolescence. The aim of the study was to determine the relationship between emotional burnout and conflict behavior strategies. To investigate the stated problem, the following methods were applied: V. Boyko’s method “Diagnosis of Emotional Burnout,” the Thomas-Kilmann Conflict Mode Instrument (TKI), an original questionnaire titled “Determining a Person’s Self-Perception in Conflict,” and methods of mathematical statistics, including Pearson’s correlation coefficient. Results. According to the results obtained using the Thomas-Kilmann method, the most frequently chosen conflict strategy among respondents was competition (30%). Cooperation and accommodation were each chosen by 20% of participants, while avoidance and compromise were less common, each selected by 15%. The results of the “Diagnosis of Emotional Burnout” method by V. Boyko showed that 32.5% of participants exhibited a fully developed emotional burnout syndrome, 47.5% were in the process of developing the syndrome, and 20% showed no signs of it. Conclusions. The study revealed a relationship between emotional burnout and the choice of conflict behavior strategies. It was found that the competition strategy had a strong positive correlation with tension (0.603) and exhaustion (0.558), while cooperation showed a negative correlation (–0.220 and –0.105, respectively), indicating a decreased tendency to cooperate under increasing stress. Avoidance was also associated with high levels of tension (0.512) and exhaustion (0.466), while compromise showed moderate correlations (0.365 and 0.489). The accommodation strategy was weakly correlated with tension (–0.145), but showed a link with resistance (0.402), which promotes internal resistance and the suppression of personal needs, thereby exacerbating emotional exhaustion (–0.320).